(untitled) (Journal of Geography and Environmental Management, 2018)
The President of the Republic of Kazakhstan, Nursultan Nazarbayev, in his annual message, on 5 October 2018 said that: «The Astana process on Syria has become practically the only effective working format for negotiations on a peaceful settlement for solving the crisis in this country». The article is devoted to the Astana process on the peaceful settlement of the military-political situation in Syria. The problem of research is topical for today, since efforts aimed at a peaceful resolution of the military and political situation were taken from the very beginning of the street protests in Syria, but all attempts to regulate the problem before the Astana process were not successful. The seven-year military-political conflict in the SAR led the country to the largest humanitarian disaster of the 21st century, as about 5.0 million Syrians became refugees. In this connection, the course of the Astana talks in chronological order was examined, in order to clarify its contribution to the settlement of this situation. Astana’s active assistance in the negotiations aimed at solving this problem was highly appreciated by the world’s leading experts. This process created favorable conditions for a political settlement based on the UN Security Council resolution. The creation of four zones of “de-escalation”, for the first time in history, managed to gather representatives of opposition groups and representatives of official Damascus at the same table, and also managed to collect the largest number of representatives of various opposition organizations. The article also outlines the positions of the countries involved in this conflict.